The entrepreneur's guide to raising capital - Nour, David, 1968- (Entrepreneur's guide (Westport, Conn.), 2009)
Ask any established business owner to identify his or her toughest challenge when just starting out, and you'll likely get this answer: raising capital. Most aspiring entrepreneurs know far too little about the sources of money that can help start a business or fuel its growth. Where do you get capital? What are investors looking for? How do you ask for money in a way that gets results? This book answers these and many other critical questions. Even more important, entrepreneur and consultant David Nour shows how to develop long-term relationships with financial partnerÑthe people who can help.